Narrow Band Ultraviolet B on Psoriasis Vulgaris: A Systematic Review - HUSSEIN MOGAHED, HUSSIEN GAMAL; SABER YOUNIS, MOHAMED AHMED; AMANY REFAAT MOHAMED, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Psoriasis is a chronic inflammatory skin disease affecting a significant proportion of the global population. Narrowband ultraviolet B (NB- UVB) phototherapy is a widely used treatment modality. This study was carried out to systematically review the evidence on the efficacy and safety of NB-UVB phototherapy in adults with psoriasis vulgaris. Methods: A systematic literature search was conducted in fived at a bases (PEDro, PubMed, Scopus, Web of Science, and the Cochrane Library) from January 2005 to April 2024. Randomized controlled trials (RCTs) comparing NB-UVB with control interventions were included. Methodological quality was assessed using the PEDro scale. Results: Five RCTs met the inclusion criteria. Due to heterogeneity in study designs and intervention protocols, a meta-analysis was not performed; instead, a narrative synthesis was conducted. The review found that NB-UVB consistently reduced PsoriasisArea and Severity Index (PASI) scores. Three weekly sessions appeared sufficient for achieving clinically significant reductions. Both percentage-based andfixed-doseregimensyieldedcomparableoutcomes.Seleniumsupplementation did not enhance NB-UVB efficacy. Conclusion: This systematic review supports NBUVB as an effective therapy for reducing PASI in psoriasis vulgaris, but we can’t say assertively that NBUVB can be a reliable monotherapy in treatment of psoriasis vulgaris because of the heterogeneous data which didn’t help to proceed and make a meta-analysis and the small number of included studies as we included randomized control trials only. Keywords: Narrow band Ultraviolet B ,Phototherapy, Psoriasis Vulgaris.